Community Empowerment and Tax Law Reform in Strengthening Consumer Protection: A Comparative Study of Indonesia, Nigeria, and India - Anik Kunantiyorini; Dwi Edi Wibowo; Achmad Soeharto; Geraldha Islami Putra Disantara; Uche Nnawulezi; Uzodinma Yurriens Ezenduka (Universitas Negeri Semarang, 2026)
The rapid expansion of the digital economy has intensified consumer protection challenges in developing countries, particularly in cross-border digital transactions where information asymmetry, price opacity, and limited regulatory capacity expose consumers to unfair commercial practices. While tax law has traditionally been regarded as an instrument for generating state revenue, its regulatory function offers significant potential to strengthen consumer protection in digital markets. This study examines the construction of tax law as a consumer protection instrument in Indonesia, India, and Nigeria, analyzes the role of community empowerment in supporting responsive tax reform, and formulates an integrated policy model based on a functional comparative approach. This research employs normative legal research using comparative, statutory, and conceptual approaches. The comparative analysis adopts the functional comparative method developed by Konrad Zweigert and Hein Kötz, while legal materials consist of legislation, judicial and policy documents, academic literature, and relevant institutional reports. The findings demonstrate that the three jurisdictions adopt different approaches to integrating tax law with consumer protection. Indonesia emphasizes market neutrality through digital value-added tax reform, India explicitly protects consumers through anti-profiteering provisions under the Central Goods and Services Tax Act 2017, whereas Nigeria primarily prioritizes fiscal revenue mobilization with limited consumer-oriented safeguards. The study further reveals that responsive regulation, co-regulation, fiscal literacy, and community participation significantly influence the effectiveness of tax law beyond formal legal norms. Accordingly, this study proposes an integrated model of responsive tax governance that combines substantive tax justice, co-regulatory institutional arrangements, community empowerment, and digital transparency mechanisms to strengthen consumer protection in digital commerce while accommodating the legal pluralism and institutional diversity of developing countries. This is in line with Sustainable Development Goals (SDGs) 12: Responsible Consumption and Production.